Odontogenic tumors: where are we in 2017 ? - John M. Wright; Merva Soluk Tekkeşin (Istanbul University, 2017)
Odontogenic tumors are a heterogeneous group of lesions of diverse clinical behavior and histopathologic types, ranging from hamartomatous lesions to malignancy. Because odontogenic tumors arise from the tissues which make our teeth, they are unique to the jaws, and by extension almost unique to dentistry. Odontogenic tumors, as in normal odontogenesis, are capable of inductive interactions between odontogenic ectomesenchyme and epithelium, and the classification of odontogenic tumors is essentially based on this interaction. The last update of these tumors was published in early 2017. According to this classification, benign odontogenic tumors are classified as follows: Epithelial, mesenchymal (ectomesenchymal), or mixed depending on which component of the tooth germ gives rise to the neoplasm. Malignant odontogenic tumors are quite rare and named similarly according to whether the epithelial or mesenchymal or both components is malignant. The goal of this review is to discuss the updated changes to odontogenic tumors and to review the more common types with clinical and radiological illustrations.